EFL Learners' Views on Innovative Meaning-Making through Multimodal Composition: Affordances and Constraints - Nita, Fatma Rahayu; Nugroho, Him’mawan Adi (Language Circle: Journal of Language and Literature, 2023)
This current study explored the findings from the learners' views and experiences while creating a multimodal composition, particularly the affordances and the constraints. A qualitative analysis was used in this study as it analyzed the narratives of 15 (fifteen) learners who responded to an open-ended questionnaire. The findings reveal that most learners positively perceived the multimodal composition since they could learn differently, an innovative meaning-making. Second, several affordances of creating multimodal composition are learning through multimodal composition, innovative meaning-making, understanding the information easily, collaboration, and attracting the reader's attention. Apart from the affordances, the learners also encounter a few constraints: struggling with meaning-making, collaboration with peers, and putting the idea. Relatedly, the teachers could use these results as their reflection in utilizing multimodal composition in the class. First and foremost, multimodal composition offers a new perspective of innovation in ELT context which could be applied in teaching and learning process.